Adjuvant radiotherapy in retroperitoneal sarcomas. A Scandinavian Sarcoma Group study of 97 patients. (September 2014) - Trovik, Linn H.; Ovrebo, Kjell; Almquist, Martin; Haugland, Hans Kristian; Rissler, Pehr; Eide, Johan; Engellau, Jacob; Monge, Odd R.; Nyhus, Anniken B.; Elde, Ingvild K.; Jebsen, Nina L.
Abstract: Background. Currently there is no consensus on the use of adjuvant radiotherapy (RT) in retroperitoneal sarcoma (RPS). We have analysed clinical outcomes in patients with localised RPS treated at two Scandinavian Sarcoma Group (SSG) centres: Haukeland University Hospital (HUH), Bergen, Norway and Skåne University Hospital (SUH), Lund, Sweden to clarify the effects of adjuvant RT on local control and overall survival (OS). Material and methods. Local databases and registers at HUH and SUH as well as the SSG central register were used to identify RPS patients. Patients with localised RPS who underwent surgery in Bergen between 1988 and 2009 and in Lund from 1998 to 2009 were included. Medical records were examined for clinical data, tumour characteristics, treatment factors and follow-up status. Archived tumour sections and tumour tissue were reviewed, and when necessary, restained and reclassified. Cox regression was used to analyse the association of potential prognostic factors with local recurrence-free survival (LRFS), metastasis-free survival (MFS) and OS. Results. The study included 97 patients: 52 from Norway and 45 from Sweden. The proportion of high-grade tumours was 73%. The five-year LRFS, MFS and OS were 55%, 59% and 60%, respectively. RT was significantly associated with improved local control resulting in a five-year LRFS of 77% compared with 39% without (p < 0.001). Furthermore, five-year OS was 71% in the RT group in contrast to 52% with surgery alone (p = 0.019). In the adjusted analysis RT proved to be a significant factor also for MFS (HR = 0.42, 95% CI 0.20–0.88, p = 0.021). In addition, high-grade malignancy, large tumour and positive surgical margin were risk factors for local recurrence. High malignancy grade was the only significant adverse prognostic factor for metastasis. High age and high-grade malignancy were negative prognostic factors for OS. Conclusion. Adjuvant RT was significantly associated with an improved five-year LRFS and OS.